The Chittagong Hill Tracts : falconry in the hills - Belal, Khaled; Rahman, Mirza Zillur; Masbah Uddin, G. M. (Chittagong : s.n., 1992)
Comprises articles and newspaper editorials on the political and socioeconomic developments in Chittagong Hill Tracts District, Bangladesh.
Keywords: Chittagong Hill Tracts (Bangladesh : Region) -- Politics and government; Chittagong Hill Tracts (Bangladesh : Region) -- Economic conditions